XMM-Newton detection of the supernova remnant G304.6+0.1 (Kes 17) - Combi, Jorge Ariel (2010)
Aims: We report the first detailed X-ray study of the supernova remnant (SNR) G304.6+0.1, achieved with the XMM-Newton mission. Methods: The powerful imaging capability of XMM-Newton was used to study the X-ray characteristics of the remnant at different energy ranges. The X-ray morphology and spectral properties were analyzed. In addittion, radio and mid-infrared data obtained with the Molonglo Observatory Synthesis Telescope and the Spitzer Space Telescope were used to study the association with the detected X-ray emission and to understand the structure of the SNR at differents wavelengths. Results: The SNR shows an extended and arc-like internal structure in the X-ray band without a compact point-like source inside the remnant. We find a high column density of NH in the range 2.5-3.5 × 1022 cm -2, which supports a relatively distant location (d ≥ 9.7 kpc). The X-ray spectrum exhibits at least three emission lines, indicating that the X-ray emission has a thin thermal plasma origin, although a non-thermal contribution cannot be discarded. The spectra of three different regions (north, center and south) are well represented by a combination of a non-equilibrium ionization (PSHOCK) and a power-law (PL) model. The mid-infrared observations show a bright filamentary structure along the north-south direction coincident with the NW radio shell. This suggests that Kes 17 is propagating in a non-uniform environment with high density and that the shock front is interacting with several adjacent massive molecular clouds. The good correspondence of radio and mid-infrared emissions suggests that the filamentary features are caused by shock compression. The X-ray characteristics and well-known radio parameters indicate that G304.6+0.1 is a middle-aged SNR (2.8-6.4) × 104 yr old and a new member of the recently proposed group of mixed-morphology SNRs.